Using an educational method according to special exercises to perform the skill of bow and develop flexibility for cub wrestlers in Iraq - Mohammed Khalid Awad,; Khulood Juma Qasim,; Shaima Habib Ali, (Eximia, 2024)
creating unique exercises utilizing a teaching approach that works with the research sample, determining how special exercises affect the development of torso flexibility, and determining how special exercises affect the development of bow ability. Activate the search The results of the pre- and post-tests for the control and experimental research groups show a statistically significant association that is favoring the post-test in the development of bow skill performance Using the experimental technique, the researcher set up one group and gave them two tests (pre and post) based on scientific theories that made sense for the topic at hand. Forty adolescent wrestlers from the Adhamiya Club in the Baghdad Governorate were recognized by the researcher. The researcher selected, at a ratio of 20, an age group consisting of only those between the ages of 12 and 14. 50% are wrestlers of the research's initial population. In terms of gathering data, the researcher employed the intended approach—the stretcher. Because the created educational technique is simple to use and produces accurate numerical results, the researchers came to the conclusion that it has demonstrated its potential to increase the flexibility of the thoracic muscles. The study suggests that sports clubs incorporate instructional techniques into their training programs.